Molecular dietary analysis of two sympatric carnivoran species, the leopard cat (Prionailurus bengalensis) and the yellow-throated marten (Martes flavigula), in Mt. Jeombongsan, Korea - Kim, Jihee; Park, Sangkyu (Mammal Study, 2024)
To investigate diets of two sympatric carnivoran species, a leopard cat (Prionailurus bengalensis) and a yellow-throated marten (Martes flavigula), in Mt. Jeombongsan, Korea, we elucidated their diet compositions using fecal DNA. Their feces were collected from October 2015 to October 2018. After extracting DNA from fecal samples, the mitochondrial 12S rRNA gene of vertebrates and the rbcL regions from plants were amplified. Prey DNA was detected by cloning-based sequencing using blocking primers. A variety of rodents such as Muridae and Cricetidae and birds such as Passeriformes and Galliformes were frequently detected in feces of leopard cats and yellow-throated martens, suggesting that these taxa were important prey of the two carnivoran species. Regarding plant food sources, genus Prunus was frequently detected in feces of the leopard cat and genus Actinidia in feces of the yellow-throated marten, indicating that these two Carnivora species were not exclusively carnivorous. The maximum numbers of vertebrate prey taxa were estimated using rarefaction curves. Our results suggest that both species have roles as top predators in Mt. Jeombongsan, demonstrating significant differences in the diets of the two sympatric Carnivora species.
Keywords: Carnivora; diet composition; fecal DNA; non-invasive approach; temperate ecosystem